Using multimedia in education - Yādava, Vijaya (Pragun Publications, 2006)
There have been many experiments and innovations in the field of education and training regarding knowledge delivery. From face to face to virtual education, different technologies have played great roles at different times. In the last two decades, due to the advent of computer technologies, information delivery has got new meaning. Development, access, and transfer of text, sound, and video data have given a unique face to classrooms, libraries, and training and resource centres, in the form of interactive multimedia learning.